Cultural Heritage and Globalization: Trajectory, Projects, and Strategies of the Santa María la Real Foundation (Aguilar de Campoo, Castile, and León, Spain) - González, Jaime Nuño (International Relations and Heritage: Patchwork in Times of Plurality, 2021)
In 1977, an association was founded to restore the ruins of a medieval monastery located in the small town of Aguilar de Campoo (Palencia, Castile and León, Spain) and turn it into the hub of cultural engagement of a progressively depopulated region with scarce economic resources but a remarkably rich cultural heritage. This original initiative has since led to an enormous wealth of activity, and the Santa María la Real Foundation, heir to that association, has diversified the fields in which it works, extending its activities throughout Spain and other countries. The link with Romanesque art, one of the hallmarks of the Aguilar region, has always remained very much alive, although its reach is now much greater, notably through the publication of an ambitious work, the now benchmark “Enciclopedia del Románico en la Península Ibérica” (Encyclopedia of the Romanesque in the Iberian Peninsula). The international impact of this foundation, in an increasingly globalized world with greater demand for culture and heritage, is growing, with activities in different fields and a wide range of projects. However, the roots and ideological foundations that drove those who, more than forty years ago, with no funds but with a tremendous amount of enthusiasm, decided that the role civil society plays is crucial when raising awareness about and conserving heritage and that this cultural wealth, far from being a burden, should be understood as an enormous resource, have never been forgotten. This is what they believed, and they got right to work.
Keywords: aguilar de campoo

The monastery of Santa Maria la Real (Aguilar de Campoo, Palencia): archaeology and architecture - Matesanz Vera, Pedro (Religion and belief : a Conference on Medieval Archaeology in Europe, 21-24th September 1992 at the University of York, 1992)
Keywords: aguilar de campoo